Economics of Potato Production in Rural Area of Ilam District, Nepal - Shrestha, Keshav Prasad; Adhikari, Surya Prasad; Yadav, Surendra (International Journal of Applied Sciences and Biotechnology, 2018)
Potato (Solanum tuberosum) is grown worldwide in more than 150 countries of the world as staple food including Nepal. It is important food crops for food security and fourth most important staple food in Nepal. It contributes 2.17 in Gross Domestic Products and 6.57 in Agriculture Gross Domestic Products. The NARC has established Agriculture Research Station in Jaubari Ilam in 2014 and conducting research mainly on potato. The main objective of this study was to identify the situation of potato cultivation in the vicinity of station and suggest future activities on potato research. The field study was conducted in surroundings of five locations of the station in the hills and mountain area. In each location 35 potato growing respondents were selected randomly for the semi-structured questionnaire survey. One focus group discussion was also made in each location for the triangulation of the household information. Data were analyzed using SPSS, Strata and excel software. The result shows that the average landholding of the respondents was 2.25 ha on which they used 0.218 ha for the potato and produce average of 1208 kg. The productivity in the area was 5.6 tons which is only about 40% of the national and district productivity. It was due to the use of local variety having low yielding and susceptible to disease like wart, late blight, and scab. The benefit cost of local cultivar found 0.68 whereas improved varieties 1.73. The regression model analysis shows that if improved variety planted by the farmers, there will be 21% increased production. Similarly, training also influence on increase the productivity by 33% whereas the membership of cooperative and group increases 34% of production. Int. J. Appl. Sci. Biotechnol. Vol 6(4): 344-350